Implementasi Enkripsi Advanced Encryption Standard (AES-128) Mode Cipher Block Chaining (CBC) sebagai Keamanan Komunikasi Pergerakan Robot Humanoid KRSBI - Achmad Sudrajat; Yoyok Heru Prasetyo; Mila Kusumawardani (Jurnal Jaringan Telekomunikasi, 2021)
A humanoid robot is a robot that has a human-like shape, which has a body and head, two arms and two legs that allow it to move and interact with the environment created by humans [1]. The humanoid soccer robot system currently used still uses the Robot Operating System (ROS) system, which is basically in the system without any encryption or data security every time communication is made by sending and requesting or what is commonly called Publish and Subscribe. In order to develop the humanoid soccer robot, this research is designed for "Implementation of Advanced Encryption Standard (AES-128) Cipher Block Chaining (CBC) Mode as Communication Security for Humanoid Robot Movement KRSBI". Which is designed to operate in low quality connectivity, with network bandwidth that secures every node running on the ROS which includes features for subscribing to topics and also publishing topics. Then with the addition of cryptography can keep data or messages safe when sent, from sender to receiver without experiencing interference from third parties. According to Bruce Scheiner in his book "Applied Cryptography", cryptography is the science and art of keeping messages secure. [2] So all communications are encrypted using Secure Sockets Layer (SSL), or more specifically Transport Layer Security (TLS).